2018
DOI: 10.1371/journal.pone.0193384
|View full text |Cite
|
Sign up to set email alerts
|

Performance of glomerular filtration rate estimation equations in Congolese healthy adults: The inopportunity of the ethnic correction

Abstract: Context and objectiveIn the estimation of glomerular filtration rate (GFR), ethnicity is an important determinant. However, all existing equations have been built solely from Caucasian and Afro-American populations and they are potentially inaccurate for estimating GFR in African populations. We therefore evaluated the performance of different estimated GFR (eGFR) equations in predicting measured GFR (mGFR).MethodsIn a cross-sectional study, 93 healthy adults were randomly selected in the general population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…21 Previous data from Africa (and African European) also suggested that such an ethnic factor was not valuable. [18][19][20][21][22]29,30 Regarding ethnicity, we showed that FAS SCr af had the same global performance as FAS SCr observed in Whites, both in patients with low GFR values and in subjects with high GFR values. This is easily explained, as Q af was not different from the Q values observed in Whites.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…21 Previous data from Africa (and African European) also suggested that such an ethnic factor was not valuable. [18][19][20][21][22]29,30 Regarding ethnicity, we showed that FAS SCr af had the same global performance as FAS SCr observed in Whites, both in patients with low GFR values and in subjects with high GFR values. This is easily explained, as Q af was not different from the Q values observed in Whites.…”
Section: Discussionsupporting
confidence: 52%
“…In DRC, healthy persons were randomly selected from the general population as described elsewhere. 19 Healthy subjects were all those who did not have hypertension, diabetes mellitus, obesity, urinary abnormalities, and impaired renal function (GFR <60 or >130 ml/ min per 1.73 m 2 ). Patients with CKD were recruited from the general population and from the medical services (Renal Unit of Kinshasa University Hospital).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…New equations can be useful not only for CKD patients but also for other special cases which are not covered by the present creatinine-based GFR-estimating formulas, such as nonwhite, non-African American, despite ethnic correction [28,29]. During the past decade, alternative markers for GFR, such as cystatin C (CysC), B2 microglobulin (B2M), betatrace protein (BTP), and others have emerged [27,[30][31][32][33][34].…”
Section: Novel Filtration Markers On the Evaluation Of Residual Kidnementioning
confidence: 99%